2021
DOI: 10.3389/fendo.2021.746602
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interferon Beta-1b Therapy on Thyroid Function and Autoimmunity Among COVID-19 Survivors

Abstract: BackgroundSome studies have indicated that interferon (IFN) may be valuable in COVID-19. We aimed to evaluate the impact of short-term IFN on incident thyroid dysfunction and autoimmunity among COVID-19 survivors.MethodsWe included consecutive adults without known thyroid disorder admitted to Queen Mary Hospital for COVID-19 from July 2020 to January 2021 who had thyroid function tests (TFTs) and anti-thyroid antibodies measured both on admission and at three months.Results226 patients were included (median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The thyroid disorders caused by COVID-19 has been widely demonstrated. 36,37 HTCBSA is one of the major subtypes of hypothyroidism. Some previous studies have provided evidence of COVID-19-related hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid disorders caused by COVID-19 has been widely demonstrated. 36,37 HTCBSA is one of the major subtypes of hypothyroidism. Some previous studies have provided evidence of COVID-19-related hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…While the large multicentre trial coordinated by the World Health Organization (WHO) failed to demonstrate clinical benefits with interferon treatment in hospitalized COVID-19 patients [ 37 ], it could be explained by the delayed treatment. Hence, it is clinically relevant to evaluate the safety of interferon treatment, including thyroid-specific outcomes, which inform the potential need for surveillance, as our previous 3-month follow-up study demonstrated a modest increase in anti-thyroid antibody titres among interferon-treated patients [ 9 ]. Interferon-beta has also been used in multiple sclerosis as chronic maintenance therapy and reported to be associated with incident thyroid dysfunction and autoimmunity, mainly during the first year of treatment [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone [ 25 ] and subcutaneous low-molecular-weight heparin [ 26 ] were added at physicians’ discretion as clinically indicated. Interferon beta-1b was given once daily subcutaneously at a dose of 16 million IU [ 9 ]. The decision to use interferon beta-1b was not influenced by the baseline thyroid function and antibody levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation